2008
DOI: 10.1039/b810599e
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of argon–hydrogen Grimm-type glow discharges

Abstract: Computer simulations have been performed to describe the effect of small admixtures of hydrogen to an argon glow discharge in the Grimm-type configuration. The two-dimensional density profiles of the various plasma species (i.e., electrons, Ar + , ArH + , H + , H 2 + and H 3 + ions, H atoms and H 2 molecules, Ar metastable atoms and sputtered Cu atoms) are presented for 1% H 2 added to the argon glow discharge, and the effect of different H 2 additions (varying between 0.1 and 10%) on the species densities, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…The model calculations yielded an ionic distribution dominated by Ar + , with ArH + and H 3 + having also a significant presence, and with very small amounts of H + and H 2 + . Qualitatively similar ion distributions were also obtained in the modeling of a higher pressure (850 Pa) Grimm type dc discharge 11 and of a capacitively coupled radio frequency (rf) discharge 12 operated at lower pressures (7-33 Pa). The results of these models were of great help for the identification of key processes in the discharges, but could not be directly compared to experimental measurements.…”
Section: Introductionsupporting
confidence: 54%
“…The model calculations yielded an ionic distribution dominated by Ar + , with ArH + and H 3 + having also a significant presence, and with very small amounts of H + and H 2 + . Qualitatively similar ion distributions were also obtained in the modeling of a higher pressure (850 Pa) Grimm type dc discharge 11 and of a capacitively coupled radio frequency (rf) discharge 12 operated at lower pressures (7-33 Pa). The results of these models were of great help for the identification of key processes in the discharges, but could not be directly compared to experimental measurements.…”
Section: Introductionsupporting
confidence: 54%
“…This shorter time in the after-peak domain of the 1 H 3 + ion signal could be attributed to the presence of H 2 in the plasma gas, which reduces the time for 40 Ar 1 H + production and, consequently, for 1 H 3 + ions production through the proton transfer mechanism between 40 Ar 1 H + and H 2 . 24 Therefore, it could be stated that the effect of the molecular hydrogen added to the discharge gas on the 1 H 3 + pulse profile seems to play a more important role than the hydrogen sputtered directly from the sample.…”
Section: Influence Of Endogenous and Exogenous Hydrogen On The Pulse ...mentioning
confidence: 99%
“…hydrogen, nitrogen, or water vapour) coming from the discharge gas, the GD source, or directly from the sample, has been observed to have a large effect on the ion production and sputtering rates in GD-MS analyses. 105,106 It has been reported that the sample sputtering rates decreased when hydrogen was added to the discharge in spite of working at constant applied electrical conditions. 107 Moreover, the ion intensities for the different species present in the discharge were enhanced at increasing hydrogen concentrations up to 10%.…”
mentioning
confidence: 99%